Biosorption of Fe (II) Ions from Aqueous Solution using Kepok Banana Peel (Musa acuminate) - Djamilah Arifiyana; Vika Ayu Devianti (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2021)
The present study used adsorbents from Kepok banana peel to remove Fe (II) from an aqueous solution. The effect of adsorbent dose and initial metal concentration was investigated at room temperature to evaluate the maximum adsorption and adsorption capacity of Kepok banana peels. The adsorption parameters studied were adsorbent mass [0.5-2.5 g], and initial Fe (II) concentration [30-70 mg/L], where the operating conditions were 50 ml of Fe metal solution was added to each adsorbent, the pH value of the mixture was adjusted to 6. Then the mixture was stirred at 250 rpm for 30 minutes. In the adsorption process, it was found that 2.5 grams of mass adsorbent and 60 mg/L as initial metal concentration gave the highest adsorption and adsorption capacity, with 57.99% and 0.644 mg/g, respectively. FTIR spectra of adsorbent showed hydroxyl, carboxylic, and amine groups in Kepok banana peels. This study showed that Kepok banana peels had good potential for removing Fe (II) ions and could be used as a good adsorbent for removing the Fe (II) from water and wastewater at very little concentration.